Epidemiologia molecular e resistência a antimicrobianos de cepas de Salmonella isoladas de amostras clínicas em hospitais de São Paulo - Oliveira, Vinicius Gomes de Sales [UNIFESP] (2016)
The genus Salmonella is widely distributed in nature and may be easily found in a diverse range of foods. Currently more than 2,600 serotypes are cataloged, among which more than 1,500 belong to enterica species, subspecies enterica, and are considered potentially pathogenic for both man and animal. It is known that major of the Salmonella infections are associated with consumption of contaminated food. Worldwide, it is estimated to occur annually between 200 million and 1.3 billion of intestinal disease events. Regards to bacterial resistance, the rates in both strains isolated from clinical specimens and veterinary origin, has grown considerably. It is believed that there is a direct connection between the resistance profile and phylogeny of the strains involved in clinical and veterinary descriptions. We studied 85 strains of Salmonella spp. of human origin, isolated at three hospitals located in the cities of São Paulo, from 2008 to 2013 by disk diffusion, molecular typing (Ribotyping and Automated Multi Locus Sequence Typing) and survey of resistance genes by methods of Micro-Chip (Check Points®), Conventional Reaction Polymerase Chain (PCR) and sequencing gene. There were 23 different sorovars. The four most prevalent sorovars, in descending order, were Enteritidis (30), Typhimurium / 4, [5], 12: i: - (13), Typhimurium (8) and Muenchen (6) .The most prevalent ribogrups in the four more described sorovars, cited above, were: 259-S-3 in sorovar Enteritidis, 203-S-3 in sorovar Typhimurium 3/4, [5], 12: i: - 361-S-8 in sorovar Typhimurium and 208-S-5 in sorovar Muenchen. The four samples typed by MLST technique showed the following ST's: ST19, ST121, ST11 and ST1921. Resistance to ampicillin was found in 20.25% of the samples and 6.25% for ceftriaxone. The following resistance genes were identified in at least one of the strains: blaCMY-1, blaCMY-2 blaTEM, blaCTX-M-14, blaCTX-M-1 blaSHV, blaGES. The resistance to ciprofloxacin was observed in 6,25% of the samples. There was a similarity in the resistance profile from samples of clinical origin and veterinary source samples, which were previously studied from the Pathogen Reduction Program (PRP) of the Ministry of Agriculture, Livestock and Supply (MAPA). As for the sorovars identified, more was observed in veterinary samples (53) compared to sorovars described in samples of clinical origin (23) with a predominance of sorovar Enteritidis and Typhimuirum. Of the four ST?s identified in samples of clinical origin, ST19 was also described in veterinary samples.